The nurse educator role in Australian hospitals: Implications for health policy - Sayers, J.; Digiacomo, Michelle (Royal College of Nursing Australia, 2010)
To date, the nurse educator role in the Australian hospital setting has been poorly described. Current pressures for health care reform have prompted reviews of nursing roles. This paper discusses the literature pertaining to the nurse educator role within the context of the Australian health care environment and current health care policy. Building on this synthesis, barriers and facilitators impacting on the nurse educator role are identified and strategic directions for policy, role clarification and advanced practice role development are highlighted. Further research identifying the impact of the hospital-based nurse educator on patient outcomes and professional nursing practice are proposed. Crown Copyright © 2010 Published by Elsevier Australia (a division of Reed International Books Australia Pty Ltd) on behalf of Royal College of Nursing, Australia. All rights reserved.